A Candida albicans regulator of disseminated infection operates primarily as a repressor and governs cell surface remodeling. Issue 2 (19th February 2016) - Böhm, Lena; Muralidhara, Prathibha; Pérez, J. Christian
Summary: Virulence traits are often controlled by transcription regulators, i.e. sequence‐specific DNA‐binding proteins. The regulators that sustain microbial proliferation in the host typically work by promoting the expression of the genes that mediate such traits. Here, we report a singular example in the human fungal pathogen Candida albicans in which a transcription regulator functions by repressing the expression of virulence genes, yet its overall role is to promote virulence. We explain this apparent paradox by establishing that a major function of this protein, Zcf21p, is to set a default state of low expression of multiple cell wall components which include virulence determinants. These components comprise GPI‐anchored proteins, adhesins and enzymes that synthesize cell wall sugar decorations. Deletion or overexpression of ZCF21 results in cell wall structure modifications that influence recognition and elimination of the fungus by macrophages. By leveling off the expression of adhesins, ZCF21 also prevents C. albicans self‐aggregation. Balancing the expression of cell wall components – virulence determinants included – is, therefore, critical for C. albicans to assemble a cell surface configuration that is suitable to colonize mammalian tissues and evade immune surveillance. Abstract : A regulatory protein known to contribute to the establishment of C. albicans disseminated infections is shown here to negatively control the expression of cell surface components, several of which promote virulence. Balancing the expression of cell wall constituents—virulence determinants included—is therefore key to produce a cell surface configuration suited to mount systemic infections.